2004
DOI: 10.4269/ajtmh.2004.70.197
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Assessment of 24 Monthly Doses of Rifampin, Ofloxacin, and Minocycline Versus Two Years of World Health Organization Multi-Drug Therapy for Multi-Bacillary Leprosy

Abstract: Monthly doses of rifampin, ofloxacin, and minocycline (ROM) are expected to be effective treatment for multi-bacillary leprosy. Patients with MB leprosy received ROM (n = 10) or World Health Organization multi-drug therapy (MDT) (n = 11). Treatment with ROM was given as 24 consecutive monthly observed doses of rifampin (600 mg), ofloxacin (400 mg), and minocycline (100 mg). Treatment with MDT was given as 24 consecutive monthly observed doses of rifampin (600 mg) and clofazimine (300 mg), and unobserved daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 17 publications
0
43
0
3
Order By: Relevance
“…(11) Research conducted by Haryanto et al have shown a significant correlation between adherence to treatment MDT with laboratory test results. (12) ROM regimens has a high level of compliance because it is not taken daily regimens and shorter treatment duration (13) Based on morphology index shows only 1 (4.8%) samples with MI of 0.5%, whereas 20 (95.2%) samples with MI 0. In lepromatous leprosy, morphology index fell from a starting point of about 5-20% to zero after 5-6 months of uninterrupted treatment with dapsone, or after about five weeks of combination therapy regimens using rifampicin.…”
Section: Discussionmentioning
confidence: 99%
“…(11) Research conducted by Haryanto et al have shown a significant correlation between adherence to treatment MDT with laboratory test results. (12) ROM regimens has a high level of compliance because it is not taken daily regimens and shorter treatment duration (13) Based on morphology index shows only 1 (4.8%) samples with MI of 0.5%, whereas 20 (95.2%) samples with MI 0. In lepromatous leprosy, morphology index fell from a starting point of about 5-20% to zero after 5-6 months of uninterrupted treatment with dapsone, or after about five weeks of combination therapy regimens using rifampicin.…”
Section: Discussionmentioning
confidence: 99%
“…The drug price may become a differentiating factor in choosing the drug regimen for the leprosy patients despite the side effect and drug consumption frequency. 9 The ROM regimen has a higher price with less side effects (nausea and vomiting), with once in a month drug consumption, making it more simple for the patients compare to MDT-WHO regimen which needs to be consumed every day with more side effects (skin hyperpigmentation, hemolytic anemia, methemoglobinemia, hypersensitivity reaction), but given freely. 10 Based on those considerations, occupations might be considered as an influencing factor in choosing leprosy medication regimen, therefore a further study needs to be conducted to prove this.…”
Section: Discussionmentioning
confidence: 99%
“…Both regimens showed the same result on both groups in every aspects examined such as clinical, bacteriological, and histopathological examination. 9 Additionally, Lockwood et al 4 suggested that a study comparing both regimens on MB type leprosy patients for 12 months to increase patient compliance, is needed. 4 This study was conducted to compare the effectiveness between ROM and MDT-WHO regimen for the first 12 months based on the MI score in MB type leprosy patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 In 1998, with mounting evidence that less than 24 months of therapy was effective, recommended duration was reduced to 1 year. 4,5 Significant controversy was recently generated following a proposal for a reduction in the length of treatment to 6 months with a standardized MDT regimen for all Hansen's disease patients. 6 Despite the WHO declaration that Hansen's disease would be eliminated as a public health problem (defined as a registered prevalence rate of less than 1 case per 10 000 population) by 2000, new cases continue to be diagnosed even outside endemic areas, 8,9 and the illness remains far from being eradicated.…”
Section: Introductionmentioning
confidence: 99%